Enhancing Understandings of Emerging Physical Education Practical Theory: Aboriginal Teacher Candidates’ Reflective Journaling Practices - Barrett, Joe; Cherubini, Lorenzo; Robinson, Dan (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
This paper describes results from a study that arose to explore, alongside Aboriginal teacher candidates, emerging physical education (PE) practical theory utilizing reflective journaling practices. Practical theory can be described as an individual’s personal and dynamic set of values, knowledge, and experience that guides, in part, teaching choices and behaviours. In the thematic analysis of teacher candidates’ reflective journals, care was taken to honour and confirm the voices of nine Aboriginal teacher candidates. Four key themes were identified: marginality (foreign activities and stereotypical expectations), cultural preservation through PE, Elder involvement in PE, and looking to the future. The results may serve to inform those with an interest in reflective practices in physical education teacher education (PETE) and/or Aboriginal teacher education.